'Neoliberalism and Political Crisis': A Postulate of the Causal Dialectics Behind the Unfolding Trumpian Crisis. Issue 4 (2nd October 2017) - Lodhi, Ali
Abstract : Neoliberalism is theorized by Marxist polymath David Harvey as a set of political economic practices—predicated upon the teological restoration of economic elite class power through policies of financial deregulation, capital liberalization, and privatization—entailing the intellectual de-legitimization of Keynesian economics, the axiomatization of neoclassical ontological and epistemological precepts regarding the primacy of the self-regulating market, and the retrenchment of the embedded welfare state. Neoliberalism has failed dramatically in its purported goal of reviving global capital accumulation since its inception in the late 20th century. Rather, its main substantive economic achievement has been to redistribute, rather than to generate, wealth and income. Furthermore, within academia, the neoliberal political-economic meta-structure is considered to have eroded the Western socio-cultural ethos writ large, thus irrevocably producing a combustible political environment in which an emergent proto-fascist insurgency—reified currently throughout the contemporary Western polity by the likes of Donald Trump and Marine Le Pen—may unfold. These conditions were effectuated by myriad mechanisms, however, most prominently by those which fall under the prescript of 'accumulation by dispossession'. This pertains to the continuation and proliferation of capital accumulation practices which Marx had deemed as 'primitive' or 'primal' during the emergence of the capitalist mode of production. Broadly, these entail the commodification and privatization of land; transmutation of various forms of property rights (common, collective, state, etc.) into exclusive property rights (and the subsequent extraction of rents in the case of patents and intellectual property rights); erasure of many common property rights (e.g. state pensions, paid vacations, and access to education and health care); commodification of labor power and suppression of indigenous forms of production and consumerism; imperial procedures of appropriation of assets; liquidation of exchange and taxation; and usury, the national debt and the use of the credit system as a means for accumulation by dispossession. The neoliberal state assumes the central role of both supporting and promulgating these practices, by way of its possessing a monopoly over violence and definitions of legality. The purpose of this paper lies in the task of further elucidating these mechanisms, within the context of the contemporary Western political crisis.